ANALYSIS OF THE MOST POTENTIAL WAVE ENERGY CONVERTER (WEC) HOTSPOT IN SOUTHERN SUNDA STRAIT, BANTEN, AND SUKABUMI SEAS - Alfredo Alexandro Karyoto, Jesaya
This study was conducted to find a potential location on installation of wave energy converter (WEC) in southern Sunda Strait, Banten, and Sukabumi seas by analyzing 17 years (1991 – 2007) wave power data. In this study, Simulating WAve Nearshor (SWAN) hindcast data was used with 1 hour temporal resolution and 0.03ox0.03o grid resolution. The hindcast data have already been verified with buoy data from Seawatch Project. The data was utilized to see the characteristics and variability of wave power and finding the potential WEC hotspot. Wave power variability and WEC hotspot were determined using coefficient of variation (COV), optimum hotspot identifier (OHI), wave power, depth, distance from shore, and wave development index (WEDI). The results of CoV and OHI show 20 potential location for installing WEC with stable wave power resource with mean wave power at above 20 kW/m. Further selection was carried out with selected parameter of depth and distance from the shore. It reduces the 20 locations onto 3 locations that is S6, J3, and J11. The final selection with WEDI shows that WEC’s durability and the assumed investment for WEC is relativity similiar on the 3 locations. Additional analysis with the population’s demographic presents that J11 which closest to Surade City is the most potential location for installation of terminator type WEC Wave Dragon.